Felsőoktatás-politika a Horthy-korszakban - Fizel, Natasa (Közép-Európai Közlemények, 2013)
In my study I aim to show the circumstances of the inception of “ideological” or to put it another way “parallel” departments of the University of Ferenc József, the predecessor of the University of Szeged, in the 1920s and 1930s through the accurate and entire exploration of archive sources and the use of a historical sociology perspective, which highlights through the division of the denomination of that age upon that, in fact, the efforts made in the transformation of the university in the early 1920s were not yet in accordance with variety of students of that age. My study also embraces the introduction of the denominational compound of students enrolled to the university in the 1920s, which suggests that the university students who moved from Kolozsvár to Szeged were protestant to a greater degree than the contemporary Hungarian society.